Re‐detection vs. new acquisition of high‐risk human papillomavirus in mid‐adult women. Issue 10 (4th August 2016) - Fu, Tsung‐Chieh (Jane); Carter, Joseph J.; Hughes, James P.; Feng, Qinghua; Hawes, Stephen E.; Schwartz, Stephen M.; Xi, Long Fu; Lasof, Taylor; Stern, Joshua E.; Galloway, Denise A.; Koutsky, Laura A.; Winer, Rachel L.
Abstract : To understand high‐risk (hr) human papillomavirus (HPV) epidemiology in mid‐adulthood, we assessed whether associations between incident detection of hrHPV DNA and recent sexual behavior differed according to whether or not there was serologic evidence of prior infection. From 2011 to 2012, we enrolled 409 women aged 30–50 years into a 6‐month longitudinal study. We collected health and sexual behavior histories, enrollment sera for HPV antibody testing, and monthly self‐collected vaginal swabs for HPV DNA genotyping. Generalized estimating equations logistic regression identified risk factors for type‐specific incident hrHPV DNA, stratified by type‐specific hrHPV serostatus at enrollment. Population attributable risks of hrHPV due to prior and recent exposure were estimated. When type‐specific hrHPV serology was negative, recent sexual risk behavior was positively associated with incident hrHPV DNA (odds ratio in women reporting ≥3 recent sexual risk behaviors [ e.g ., new or multiple partners] vs . no recent sexual activity = 9.8, 95% CI: 2.4–40.6). No associations with recent sexual behavior were observed with positive type‐specific hrHPV serology. Thirty percent of incident hrHPV DNA detection was attributable to prior infection (with positive serology) and 40% was attributable to recent sexual risk behavior (with negative serology). The proportion of incident hrHPV DNA detection attributable to recent sexual risk behavior decreased with increasing age. Among women with serologic evidence of prior infection, re‐detection of the same hrHPV type is likely due to reactivation or intermittent detection of persistent infection. Without serologic evidence of prior infection, new detection is likely due to new acquisition or to intermittent detection of persisting infection. Abstract : What's new? Among young women, newly detected human papillomavirus (HPV) infection typically is linked to recent sexual behavior. For mid‐adult women who have long been sexually active, however, the source of newly detected HPV infection often is unknown. Here, combined HPV serology, HPV DNA genotyping, and sexual behavior data show that incident high‐risk (hr) HPV detection in mid‐adult women is due to either probable new acquisition or re‐detection of prior infection. Incident hrHPV was strongly associated with recent sexual behavior in women seronegative for prior infection. Reactivation or intermittent detection likely accounted for incident hrHPV in women with type‐specific seropositivity.